What Can Electron Microscopy Tell Us Beyond Crystal Structures? - Zhou, Wuzong; Greer, Heather F. (European journal of inorganic chemistry, 2016)
Transmission electron microscopy is a powerful tool to directly image crystal structures. Not only that, it is often used to reveal crystal size and morphology, crystal orientation, crystal defects, surface structures, superstructures, etc. However, due to the 2D nature of TEM images, it is easy to make mistakes when we try to recover a 3D structure from them. Scanning electron microscopy is able to provide information on the particle size, morphology and surface topography. However, obtaining information on crystallinity of particles using SEM is difficult. In this microreview article, some practical cases of transmission and scanning electron microscopy investigations of inorganic crystals are reviewed. Commonly occurring uncertainties, imperfection and misunderstandings are discussed. Some examples of conventional SEM and TEM studies of inorganic crystals are reviewed. Typical problems of misinterpretation of the images are discussed.